Building 10th Grade Students’ Vocabulary through Reading the Newspaper at SMK 45 Lembang - Katemba, Caroline Victorine; Parilia, Rafael Randy (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2020)
Using newspaper either printed or online as a medium of English learning is a unique way to stimulate students’ interest in reading since most of the students at this age have dropped their interest in reading resulting their lack of English vocabulary. The researcher decided to use the newspaper as a medium to build students’ vocabulary. The researcher chose a group of participants from a group of 10th-grade students in SMK 45 Lembang, which are class XB and Class XE. The school gave these two classes as the samples because they believed each class has relatively equal knowledge and cognitive abilities. In this study, researchers randomly selected from the two classes to be used as a sample for the Control and Experimental Class. As a result, researchers found class XE as Control class and XB as the Experimental class. The study lasted for a full month, in which each class received different treatment. As a result, the Gain value of Experimental class is higher than the Control class. Moreover, based on the result of the data analysis with the Mann-Whitney U test method, it showed that there were significant differences in Students’ Vocabulary growth, between Control class and Experimental class. Based on the calculation of Non-parametric Mann- Whitney U test, the gain data between Experimental Class and Control Class show the value of Asymp Sig. (0.000), Zα (0.05) and the value of Z (4.847). Z α (1.96). Therefore, the researcher can conclude that the method of using newspaper as a teaching material has a positive impact on the absorption and growth in students’ vocabulary. Keywords: vocabulary achievement, reading, newspaper